RATIO ANALYSIS OF ACTUAL BUSINESS PERFORMANCE OF INVESTMENT FUNDS IN SERBIA - Barjaktarovic, Lidija; Jecmenica, Dejan; Paunovic, Maja (Serbian Journal of Management, 2013)
The subject of this paper is to analyze the performance of open investment funds in Serbia in the period of 2007 to 2013. By applying Jensen’s alpha, Sharper and Sortino ratio it was found that the performances of domestic investment funds are unsatisfactory. Review of investment funds operations is based on the returns they bring and the risks they accept in the business. In Serbia, the equity funds, as the most risky funds, started to operate in 2007, while cash funds (as the least risky funds) were introduced in later phase after 3 years. At the moment there are 16 open investment funds (on 02/28/13), where value growth and value maintenance funds dominate. A total net asset of open investment funds is 2,324 million Dinars i.e. 20 million Euros (at the end of 2012).